Pengaruh Suku Bunga Terhadap Bagi Hasil Deposito Mudharabah Dengan Mediasi Return On Asset (ROA) - Muhammad Arief; Rika Lidyah; M Iqbal (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2021)
This study aims to determine the effect of the Interest Rate on the profit-sharing of Mudharabah deposits with Return On Asset (ROA) as mediation at Sharia Banks in Indonesia in 2014-2018. This research uses quantitative methods. The type of data in this study is secondary data. Data collection techniques using documentation techniques. The sample selection tested in this study uses a purposive sampling method. The sample used is the quarterly financial statements in 2014-2018 at 3 Islamic commercial banks in Indonesia. In this study data analysis techniques using the SPSS 21 application. The results of this study indicate that interest rates have a positive and significant effect on the profit-sharing of Mudharabah deposits and interest rates also have a negative and significant effect on return on assets (ROA). Return On Assets (ROA) has a negative and significant effect on the profit-sharing of Mudharabah deposits. While interest rates have a positive and significant effect on the profit-sharing of Mudharabah deposits with Return On Asset (ROA) as mediation